(untitled) (ModaPalavra e-periódico, 2021)
Since the 1980s, investigative interest and advances in the field of socio-cultural and consumer trends have been growing internationally. But, so far, there is neither a methodology nor a body of research techniques established for such an activity. It is for this reason that we defend the establishment and consensus of a methodology together with a set of well-structured investigative techniques for the development of trend research. This article presents the content analysis and, later, a comparative study of the methods and techniques used until today by the main observatories of Brazilian and Spanish trends. It is also a study of the consumer sectors in which this activity is carried out and the disciplines that serve it. I study that we are beginning to extend EE. UU, United Kingdom, France, Italy and Japan. It is undoubtedly an unprecedented contribution that will lead to the establishment of the investigation of socio-cultural and consumer trends, as an essential tool within the discipline of communication.